Natural Compounds as Promising Modulators of Breast Cancer Signalling: The Significant Role of Tea Polyphenols - Roy, Anirban; Banerji, Aniruddha (Medical Science: Trends and Innovations Vol. 5, 2025)
Breast cancer, as a disease, is highly prevalent among women in India and worldwide. Aberrant expression and signalling through various pathways like the Focal Adhesion Kinase (FAK) pathway, the Mitogen-Activated Protein Kinase (MAPK) pathway and the Extracellular Signal Regulated Kinase (ERK) pathway have been reported to cause breast cancer progression and metastasis. Treatment of breast cancer patients via chemotherapy can often pose severe toxic side effects with peripheral tissue and organ damage. Determining the anti-tumorigenic potential of various natural compounds is an interesting area of work in order to address this issue. As FAK, MAPK and ERK signalling pathways are important factors in the progression and spread of breast cancers, the potential of two tea polyphenols, epigallocatechin-3-gallate (EGCG) and theaflavin was analysed for targeting these signalling pathways. Molecular docking and analysis indicated both theaflavin and EGCG showed good binding affinity and interactions via hydrogen bonding with various amino acids on the FAK, p38MAPK and ERK2 molecules. Theaflavin and EGCG however, appear to interact with different sites on p38MAPK and ERK2 but both bind around the same site on FAK. These studies indicate the potential of the tea polyphenols, theaflavin and EGCG, as signalling pathway inhibitors for the treatment of breast cancers. Further, in vitro and in vivo studies to understand the pattern of interactions of theaflavin and EGCG with these target molecules could result in positive outcomes for breast cancer treatment.